Treating intangible inputs as investment goods: The impact on Canadian GDP - Nazim Belhocine (Queen's University, Department of Economics, 2008)
National income accounts view most business expenditures on intangible goods as acquisitions of intermediate inputs that get entirely used up in the production of final output. After arguing against this convention, I construct a data set to document firms' expenditures on an identifiable list of intangible items for which there is now wide agreement among national accountants. I then examine the implications of treating intangible spending as an acquisition of final (investment) goods on GDP growth for Canada. I find that investment in intangible capital by 2002 is almost as large as the investment in physical capital. This result is in line with similar findings for the U.S. and the U.K. Furthermore, the growth in GDP and labor productivity may be underestimated by as much as 0.1 percentage point per year during this same period. The discussion on the need to capitalize intangibles and the magnitude of the findings demonstrate the necessity to report such expenditures as investments and to collect this data as an integral part of the Canadian system of national income accounts.
Keywords: E22; O33; O47; 330; Intangible Capital Goods; Intangible Investment; Gesamtwirtschaftliche Produktion; Volkswirtschaftliche Gesamtrechnung; Sozialprodukt; Vorprodukt; Immaterialgüterrechte; Investition; Kanada